Perbanyakan Agen Hayati Trichoderma Sp. Menggunakan Media Beras di Laboratorium Pengamatan Hama dan Penyakit Tanaman Banyumas - Haristia, Windi; B, Ardiana Kartika; Pribadi, Teguh (Proceedings Series on Physical & Formal Sciences, 2021)
The rhizosphere area of a plant is an area rich in microbes, one of which is a group of fungi. This practical work aims to multiply Trichoderma sp. in the rhizosphere of bamboo plants in the Jatilawang area using rice as a medium. This practical work uses rice and coconut media in conducting exploration. The results of practical work obtained spore density of Trichoderma sp. meet the standards for application in plants. Obstacles in exploring Trichoderma sp. is takes a long time.